Comparing Italian and Brazilian consumers’ attitudes towards Short Food Supply Chains - Giampietri, Elisa; Cardoso, Bárbara Françoise; Finco, Adele; Verneau, Fabio; Del Giudice, Teresa; Shikida, Pery Francisco Assis (Italian Review of Agricultural Economics, 2016)
According to the Theory of Planned Behavior, this work investigates consumers’ attitudes towards the intention to buy local food in Short Food Supply Chains (SFSCs), carrying out a survey among university students in Italy and Brazil. Results show that sustainability and food safety mostly influence consumers’ behavior in both countries. However, the main differences emerged are related to the fact that Italian consumers recognized the SFSCs as a catalyst for new employment opportunities and local development, whereas the role of short chains on life quality and wellbeing is stressed by Brazilian ones.